If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -8 = 7 + 8b Reorder the terms: -8 + 3b = 7 + 8b Solving -8 + 3b = 7 + 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. -8 + 3b + -8b = 7 + 8b + -8b Combine like terms: 3b + -8b = -5b -8 + -5b = 7 + 8b + -8b Combine like terms: 8b + -8b = 0 -8 + -5b = 7 + 0 -8 + -5b = 7 Add '8' to each side of the equation. -8 + 8 + -5b = 7 + 8 Combine like terms: -8 + 8 = 0 0 + -5b = 7 + 8 -5b = 7 + 8 Combine like terms: 7 + 8 = 15 -5b = 15 Divide each side by '-5'. b = -3 Simplifying b = -3
| 6(-2+4x)=-60 | | 9u^3/27x^5 | | 2.1z-38=10.27 | | 4/5m-3/10=3/5 | | -6=-6+3m | | 8n-5=58+n | | 3(3+2y)=39 | | 4(-6x+4)=208 | | 7x+9=41 | | -5(4x-3)+21(x-5)=-88-4 | | 3xy+2y=x-4 | | am-d=m | | Z+147=780 | | 8(6+4x)=176 | | Y=3*-7+11 | | 12/9-2 | | 5.7+1.9x=11.4 | | (-5)p+4(1-p)=(-2)p+(-3)(1-p) | | 140=4(x+10s)+30s | | 48x^2-12x-18=0 | | Z/1.22=-27 | | (3-z)(5z-1)=0 | | x(x+44)=0 | | 2.69=x-1 | | -2n(5n-7)=0 | | -(p+3)+2p-6=10 | | 4xsquared-6x-1=0 | | -6x-2(-2x-5)=-2 | | 2y^2-15y+22=0 | | (-5)p+(-2)(1-p)=4p+(-3)(1-p) | | X^2=16+[(x+4)*(x-4)] | | 6[(53)4]2= |